Aristolochia weixiensis, a new species of Aristolochiaceae from Yunnan, China - Ma, Jinshuang; Zhang, Lin; Hua, Zhi-Xiang; Chen, Guang-Fu; Liao, Shuai (Phytotaxa, 2015)
Aristolochia weixiensis, a new species from northwest Yunnan, China, is described. A. weixiensis is affinis to A. moupinensis with similar leaf shape, but differs from the latter in the limb with dark purple colour and dense papillae, ca. 3.5 cm in diam., throat with light brown colour and dense brownish red patches, 13–16 mm in diam. Meanwhile, A. weixiensis is similar to A. wuana with similar leaves in shape, but differs in fruit and the size of leaf.